Validation of NAD synthase inhibitors for inhibiting the cell viability of Leishmania donovani: In silico and in vitro approach. Issue 17 (22nd November 2019) - Mandal, Haraprasad; Vijayakumar, Saravanan; Yadav, Shalini; Kumar Singh, Shubhankar; Das, Pradeep
Abstract: NAD (nicotinamide adenine dinucleotide) synthase catalyses the biochemical synthesis of NAD, from nicotinic acid adenine dinucleotide (NAAD). NAD may be synthesized through the de novo pathways and/or the salvage pathways in cells. However, in Leishmania parasite, the synthesis of NAD solely depends on the salvage pathways. NAD synthetase is widely explored as a drug target in various microorganisms. In Bacillus anthracis, a group of sulphonamides 5599, 5617 and 5824 and complex amide 5833 were reported to have activity at micromolar range against NAD synthetase. Hence, in the present study, the same group of sulphonamides and complex amide were validated through in silico and in vitro studies for its efficiency towards Leishmania donovani NAD synthase. In silico study revealed the ligands 5824 and 5833 to have better docking score. Molecular dynamics simulation for a duration of 50 ns of all the ligand–protein complexes suggested that the complexes with the ligands 5824 and 5833 were stable and interacting. In vitro and ex vivo studies have shown that 5824 and 5833 inhibit the cell viability of the organism at a lower concentration than 5599 and 5617. Hence, with further in vivo validation, 5824 (or its synthetic analogues) and 5833 could be the choice that may work synergistically with other potential drugs in treating drug-resistant cases of leishmaniasis. Communicated by Ramaswamy H. Sarma